2013
DOI: 10.1111/saje.12035
|View full text |Cite
|
Sign up to set email alerts
|

Job Search and the Measurement of Unemployment in South Africa

Abstract: We interrogate the distinction between searching and non-searching unemployment in South Africa using data from the first national panel survey that tracks the individual. In particular, we test whether the non-searching unemployed display a weaker commitment to the labour market than the searching unemployed, and we investigate what counts as search activity. We find that over the panel, the search status of the unemployed does not predict their subsequent employment status, a result that is robust also for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…to include other factors of heterogeneity, in addition to gender, that may affect the decision of women and men to participate in the labor market after receiving the CSG. As shown by a large body of literature (Burger and von Fintel, 2014;Fourie and Leibbrandt, 2012;Kingdon and Knight, 2006;Posel et al, 2006;Posel et al, 2014, Yu, 2013a, 2013b, among many others), education influences the benefits and costs of participating in the labor market, and thus, we may expect different behavioral responses to the CSG for more-educated and less-educated women or men. In more detail, education (matriculation, in particular) encourages labor force participation and job search and increases employment prospects (Fourie and Leibbrandt, 2012) 18 A similar argument applies when considering the urban/rural dichotomy and families receiving only the CSG vs. those receiving both the CSG and the OAP (see Section 2) 19 .…”
Section: Empirical Frameworkmentioning
confidence: 99%
“…to include other factors of heterogeneity, in addition to gender, that may affect the decision of women and men to participate in the labor market after receiving the CSG. As shown by a large body of literature (Burger and von Fintel, 2014;Fourie and Leibbrandt, 2012;Kingdon and Knight, 2006;Posel et al, 2006;Posel et al, 2014, Yu, 2013a, 2013b, among many others), education influences the benefits and costs of participating in the labor market, and thus, we may expect different behavioral responses to the CSG for more-educated and less-educated women or men. In more detail, education (matriculation, in particular) encourages labor force participation and job search and increases employment prospects (Fourie and Leibbrandt, 2012) 18 A similar argument applies when considering the urban/rural dichotomy and families receiving only the CSG vs. those receiving both the CSG and the OAP (see Section 2) 19 .…”
Section: Empirical Frameworkmentioning
confidence: 99%
“…20 There is a high unemployment rate, which sits at 25.2% at the ''standard definition'' (which excludes discouraged job seekers from the definition of the unemployed) and 35.9% at the ''expanded definition'' (which includes the discouraged job seekers). 21 It is also a highly regulated country with relatively good provision of basic services such as sanitation and waste management, although these tend to be unevenly distributed. 22 The presence of a relatively sound basic services infrastructure does mean that working conditions in informal workplaces are likely to be better than in countries where such services are lacking.…”
Section: Background: Wage Work In the South African Contextmentioning
confidence: 99%
“…This broad measure of unemployment is used throughout the article. The appropriateness of this measure is discussed in Kingdon and Knight (2006) and Posel, Casale, and Vermaak (2013). 6 Finn and Leibbrandt (2013) also used a NIDS balanced panel and found that income poverty dropped significantly between waves 1 and 3.…”
Section: Source Of Data and Methodsmentioning
confidence: 99%
“…This broad measure of unemployment is used throughout the article. The appropriateness of this measure is discussed in Kingdon and Knight () and Posel, Casale, and Vermaak ().…”
mentioning
confidence: 99%